1997
DOI: 10.2466/pr0.1997.80.3c.1103
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Stress among Public School Principals in British Columbia

Abstract: 643 public school principals in British Columbia, Canada responded to a survey on administrative stress. The findings show that stress is a serious concern for these administrators. In contrast to other studies of administrative stress, "administering the negotiated contract" was a source of stress uniquely important to school principals in British Columbia. A multivariate analysis indicated that principals who had greater total scores on the measure of administrative stress perceived that administrative isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…This is consistent with findings showing that principals feel a lot of stress that frequently results in mental and physical illness (Weber, Weltle, & Lederer, 2005). The main causes of chronic strain consist of administrative tasks as reported by Canadian school principals (Allison, 1997), as well as dealing with colleagues as reported by British school principals (Cooper & Kelly, 1994). In general, school principals have diversified workloads and have to manage them in very different contexts (Mertkan, 2011(Mertkan, , 2013.…”
Section: Leading Research Questionsupporting
confidence: 83%
“…This is consistent with findings showing that principals feel a lot of stress that frequently results in mental and physical illness (Weber, Weltle, & Lederer, 2005). The main causes of chronic strain consist of administrative tasks as reported by Canadian school principals (Allison, 1997), as well as dealing with colleagues as reported by British school principals (Cooper & Kelly, 1994). In general, school principals have diversified workloads and have to manage them in very different contexts (Mertkan, 2011(Mertkan, , 2013.…”
Section: Leading Research Questionsupporting
confidence: 83%
“…In addition to overwork, Cooper and Kelley (1993) found, above all, that dealing with colleagues was the most important stress factor in over 2,600 British school principals. In the study by Allison (1997), which included 643 public school principals in Canada, it was revealed that administrative tasks were felt to be a major stress factor. According to current British estimations the annual working hours of school principals are, on average, 300-400 more than those of teachers without a headship function (Ross and Hutchings 2003).…”
Section: Discussionmentioning
confidence: 96%
“…The reason was competition among the Jewish schools because of the decreasing number of students due to demographic changes, which elicited the feeling that`t here was hostility, and we worked in splendid isolation''. Isolation was viewed by the principals as resulting in a sense of helplessness; research also sees isolation as a factor causing stress and burnout (Allison, 1997).…”
Section: The Unrelated Streamsmentioning
confidence: 99%